2010
DOI: 10.1007/s10144-010-0255-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in Norway: warm summers limit grouse reproduction

Abstract: Grouse and vole numbers may peak after peaks in the seed crop of bilberry (Vaccinium myrtillus) because of reduced levels of feeding deterrents in bilberry plants. We predicted that grouse reproduction depends also on summer (June-September) temperatures in the 2 previous years, because bilberry plants will be less exhausted after a high seed crop in or after warm summers, and thus rebuild their chemical defence more quickly. After berry peak years, population indices of capercaillie (Tetrao urogallus) and ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 42 publications
3
51
1
1
Order By: Relevance
“…In continental Europe and Britain, landuse change also refers to the intensification of agriculture and changes in grazing pressure by livestock, as well as increased browsing by ungulates. Nonetheless, within the suite of processes accompanying the population decline and reduction in cyclic amplitude, climate change (Moss et al, 2001;Ludwig et al, 2006;Selås et al, 2011) and an increase in generalist predators (Baines, 1991;Vos, 1995;Kurki et al, 1998) are factors that may also contribute to the negative trends in European woodland grouse. To date, these factors have received comparatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…In continental Europe and Britain, landuse change also refers to the intensification of agriculture and changes in grazing pressure by livestock, as well as increased browsing by ungulates. Nonetheless, within the suite of processes accompanying the population decline and reduction in cyclic amplitude, climate change (Moss et al, 2001;Ludwig et al, 2006;Selås et al, 2011) and an increase in generalist predators (Baines, 1991;Vos, 1995;Kurki et al, 1998) are factors that may also contribute to the negative trends in European woodland grouse. To date, these factors have received comparatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, response mechanisms to climate change are likely complex and highly interrelated. Such interactions and animal responses are difficult to predict in detail, but here we showed the general trends that should be expected and that are beginning to be documented elsewhere (e.g., Selås et al 2010). By modeling the basic components of fundamental niches (temperature and precipitation), we have gained some understanding of the outer bounds and drivers of potential shifts in distributions that may be expected to occur.…”
mentioning
confidence: 54%
“…- Climate warming will fundamentally alter ecosystems in Alaska, likely resulting in new species and habitat assemblages (Stralberg et al 2009, Murphy et al 2010. For example, Selås et al (2010) found that ptarmigan reproduction was negatively correlated with the preceding two summers' temperatures, and that this relationship was likely mediated by climate-induced responses at lower trophic levels. Hence, response mechanisms to climate change are likely complex and highly interrelated.…”
mentioning
confidence: 99%
“…Abundance of rodents can function as an index of predation rates if the alternative prey hypothesis (Kjellander and Nordstrom 2003;Hagen 1952) is valid. We obtained long term rodent trap data from two sites in our study area; Å motsdalen from 1991 to 2011 (Framstad 2012;Selas et al 2011) and Fuggdalen from 1974 to 2009 (Selas et al 2011) (see Fig. 1).…”
Section: Large-scale Climate Variationmentioning
confidence: 99%